2019
DOI: 10.1289/ehp4431
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Emerging and Legacy Per-/Polyfluoroalkyl Substances in Matched Serum and Semen Samples: New Implications for Human Semen Quality

Abstract: BACKGROUND: Epidemiological evidence remains equivocal on the associations between environmentally relevant levels of per-/polyfluoroalkyl substances (PFASs) and human semen quality. OBJECTIVES: We aimed to test whether the potential effects on semen quality could be better observed when seminal PFAS levels were used as an exposure marker compared with serum PFAS levels. METHODS: Matched semen and serum samples from 664 adult men were collected from a cross-sectional population in China from 2015 to 2016. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 62 publications
6
38
0
Order By: Relevance
“…Exposure to PFOA impairs human sperm motility and sperm penetration into viscous media (Sabovic et al 2020; Yuan et al 2020) and is longitudinally associated with lower sperm concentration and count and higher adjusted levels of luteinizing and follicle‐stimulating hormones in young men (Joensen et al 2009; Vested et al 2013; Song et al 2018). Serum concentrations of PFAS are also cross‐sectionally associated with deleterious markers of semen quality (Louis et al 2015; Pan et al 2019).…”
Section: Current Knowledge Of Pfas Toxicity In Humansmentioning
confidence: 99%
“…Exposure to PFOA impairs human sperm motility and sperm penetration into viscous media (Sabovic et al 2020; Yuan et al 2020) and is longitudinally associated with lower sperm concentration and count and higher adjusted levels of luteinizing and follicle‐stimulating hormones in young men (Joensen et al 2009; Vested et al 2013; Song et al 2018). Serum concentrations of PFAS are also cross‐sectionally associated with deleterious markers of semen quality (Louis et al 2015; Pan et al 2019).…”
Section: Current Knowledge Of Pfas Toxicity In Humansmentioning
confidence: 99%
“…A cross-sectional study on 212 exposed males from the Veneto region, Italy, found that increased levels of PFOA (but not PFOS) in serum and seminal fluids positively correlated with circulating testosterone and luteinizing hormone (LH), with a resultant reduction in semen quality, testicular volume, penile length, and anogenital distance [ 34 ]. A cross-sectional study from Nanjing, China [ 103 ], on 664 adult men showed that seminal PFOA and PFOS levels were significantly associated with a lower percentage of progressive sperm and higher percentage of DNA fragmentation. Use of serum PFOA and PFOS levels made their association weaker compared to the levels in seminal fluids [ 103 ].…”
Section: Studies Linking Environmentally Relevant Exposure To Malementioning
confidence: 99%
“…A cross-sectional study from Nanjing, China [ 103 ], on 664 adult men showed that seminal PFOA and PFOS levels were significantly associated with a lower percentage of progressive sperm and higher percentage of DNA fragmentation. Use of serum PFOA and PFOS levels made their association weaker compared to the levels in seminal fluids [ 103 ]. A follow-up study [ 33 ] using the same population confirmed the association between serum and semen PFOA levels with semen parameters and showed a decrease in total testosterone and free testosterone.…”
Section: Studies Linking Environmentally Relevant Exposure To Malementioning
confidence: 99%
“…PFOA is highly resistant to degradation by ecological processes, with a half‐life of 2.3–3.8 years in humans (Post et al., 2012; Shane et al., 2020; Taylor et al., 2020), with a significant cause of toxicity concern. Exposure sources include home‐grown vegetables, food and food packaging, house dust and consumer products (Choi et al., 2020; Post et al., 2012; Xiang et al., 2020), at environmentally relevant levels of 8–35 ng/L (ATSDR, 2018; Dong et al., 2009; Post, 2020), reported to be harmful to human sperm quality (Pan et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure sources include home-grown vegetables, food and food packaging, house dust and consumer products (Choi et al, 2020;Post et al, 2012;Xiang et al, 2020), at environmentally relevant levels of 8-35 ng/L (ATSDR, 2018;Dong et al, 2009;Post, 2020), reported to be harmful to human sperm quality (Pan et al, 2019).…”
mentioning
confidence: 99%